Exploring Magic Realism in `Dallergut Dream Department Store` by Miye Lee - Karman, Muhammad Taufikqul Hidayat; Supsiadji, Mateus Rudi (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
: Magic realism is a literary genre that blends the magical with the mundane to create a unique narrative style. This study explores the use of magic realism in Miye Lee's DallerGut Dream Department Store. The research employs the theoretical frameworks of Wendy B. Faris' characteristics of magic realism and Anne C. Hegerfeldt's literary techniques. Utilizing an extrinsic approach focused on both theories, the study aims to identify and analyze the characteristics and literary techniques of magic realism in the novel. A qualitative method is used for this research. The analysis reveals that Miye Lee employs irreducible magical elements seamlessly blended with the realistic world of a dream department store, creating a narrative that challenges readers' perceptions of reality. Elements such as dream products, emotional payments, and mythical creatures like Leprechauns are presented as ordinary aspects of the characters' lives, exemplifying the characteristic merging of magical and real realms. Techniques like installment and subversion, as well as playing on the fantastic, are used to maintain a balance between the real and the magical, keeping the readers in a state of wonder and hesitation. The findings demonstrate that DallerGut Dream Department Store effectively uses magic realism to delve into complex human emotions and societal issues, providing a richer depiction of reality through its fantastical elements. This study contributes to the understanding of magic realism in contemporary literature, particularly within the context of Asian literature, and paves the way for further exploration of the genre's thematic and cultural implications.